The Quality of School Wellness Policies and Energy-Balance Behaviors of Adolescent Mothers - Debra Haire-Joshu, PhD; Byron W. Yount, MA; Elizabeth L. Budd, MPH; Cynthia Schwarz, MPH, MS, RD; Rebecca Schermbeck, MPH, MS, RD; Scoie Green, MPH; Michael Elliott, PhD (Preventing Chronic Disease, 2011)
IntroductionIn this study, we 1) compared the quality of school wellness policies among schools participating in Moms for a Healthy Balance (BALANCE), a school- and home-based weight loss study conducted with postpartum adolescents in 27 states; and 2) assessed the relationship between policy quality with energy-balance behaviors and body mass index z scores of postpartum adolescents.MethodsAs a part of BALANCE, we collected data on high-calorie food and beverage consumption, minutes spent walking, and height and weight for 647 participants. The School Wellness Policy Coding Tool was used to assess the strength and comprehensiveness of school district wellness policies from 251 schools attended by participating adolescent mothers.ResultsSchools averaged low scores for wellness policy comprehensiveness and strength. When compared with participants in schools with the lowest policy comprehensiveness scores, adolescent mothers in schools with the highest scores reported consuming significantly fewer daily calories from sweetened beverages while reporting higher consumption of water (P = .04 and P = .01, respectively). School wellness policy strength was associated with lower BMI z scores among adolescent mothers (P = .01).ConclusionSchool wellness policies associated with BALANCE may be limited in their ability to promote a healthy school environment. Future studies are needed to evaluate the effect of the strength and comprehensiveness of policy language on energy balance in high-risk postpartum adolescents. Evidence from this work can provide additional guidance to federal or state government in mandating not only policy content, but also systematic evaluation.